Translatability of Scalp EEG Recordings of Duration-Deviant Mismatch Negativity Between Macaques and Humans: A Pilot Study - Tada, Mariko; Suda, Yuki; Kirihara, Kenji; Koshiyama, Daisuke; Fujioka, Mao; Usui, Kaori; Araki, Tsuyoshi; Kasai, Kiyoto; Uka, Takanori (Frontiers in Psychiatry, 2020)
Mismatch negativity (MMN) is a negative deflection of the auditory event-related potential (ERP) elicited by an abrupt change in a sound presented repeatedly. In patients with schizophrenia, MMN is consistently reduced, which makes it a promising biomarker. A non-human primate (NHP) model of MMN based on scalp electroencephalogram (EEG) recordings can provide a useful translational tool, given the high structural homology of the prefrontal and auditory cortices between NHPs, such as macaques, and humans. However, in previous MMN studies, the NHP models used did not allow for comparison with humans because of differences in task settings. Moreover, duration-deviant MMN (dMMN), whose reduction is larger than that in the frequency-deviant MMN (fMMN) in patients with schizophrenia, has never been demonstrated in NHP models. In this study, we determined whether dMMN can be observed in macaque scalp EEG recordings. EEGs were recorded from frontal electrodes (Fz) in two Japanese macaques. Consistent with clinical settings, auditory stimuli consisted of two pure tones, a standard and a deviant tone, in an oddball paradigm. The deviant and standard tones differed in duration (50 and 100 ms for the standard and deviant tones, respectively). A robust dMMN with a latency of around 200 ms, comparable to that in humans, was observed in both monkeys. A comparison with fMMN showed that the dMMN latency was the longer of the two. By bridging the gap between basic and clinical research, our results will contribute to the development of innovative therapeutic strategies for schizophrenia.